Conducting Support Groups for Bereaved People after Disaster - Rob Gordon; Sharon des Landes; Salli Trathen (Forum for Group Psychotherapies and Processes, 2024)
The social dimension of disasters is a strength and a liability. After bushfires destroyed 2,000 houses damaged 25 towns and killed 173 people in the state of Victoria, Australia on Black Saturday, 9 February 2009, community-based recovery programs were established for the thousands of people living in devastated communities. Among these were bereavement support groups to assist the grieving. They met monthly for 4 years. While therapeutic, they are not therapy groups yet require careful establishment and a technique to engage community members who would probably never have sought therapy. The technique is restrained, allows groups to find their way but to hold the purpose. The process showed a distinct rhythm with engagement through tears, humour and comradeship in adversity during the first year deepening to mutual support with recovery problems in the second year. Then in the third year, the safety of their common bonds allowed expression of the depth of anger, pain and grief. In the fourth year they were able to work on damaged identity, reflect on the lost pre-disaster life and look towards new life. The ‘group in mind’ formed gave confidence to cross the abyss created by disaster in the life continuum and begin a new future.